Pengalaman Siswa Dalam Memahami Nilai-Nilai Islam Melalui Media Pembelajaran Digital Pada Mata Pelajaran PAI - Nabilah Syaffa Ramdini (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2025)
This study aims to analyze students' experiences in understanding Islamic values ​​through digital PAI learning media with a qualitative approach. Rapid technological developments and interesting digital media innovations in learning are potential tools that are expected to improve students' understanding in learning, especially in Islamic Religious Education subjects. The results of the study show that the use of digital media in PAI learning can provide students with an understanding of Islamic values ​​such as tolerance, responsibility, honesty, and grateful. However, challenges remain, especially related to impaired focus and limited understanding if not balanced with teacher guidance. This study concludes that digital media has great potential in instilling Islamic values ​​contextually and relevantly to today's digital world of students.